Evaluation of antioxidant and free radical scavenging activities of honeybush tea (Cyclopia) - Hubbe, Michelle E. (Michelle Elzabet) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2000.